Quality cooperation between Finnish suppliers and case company - Reinikka, Joni (My University, 2021)
ABSTRACT : The purpose of this work is to investigate the quality cooperation between the case company and some small Finnish subcontractors. The author doing the research works in case company. Company has recognized the need for such research. In many areas, differences of opinion have been noted regarding the impact of cooperation and communication on quality. The focus is to be more on the subcontractors’ point of view The theory section explores the background by examining literature on the dynamics and enhancement of collaboration, quality development in the context of the case and possibly on communicating in a hierarchical environment. The empirical part was done by face-to-face interviews. Interviews were conducted with four Ostrobothnian companies. Two people from each company were interviewed. Inter-views will be recorded and then analyzed. Also, two people from two departments of the case company will be interviewed to get case company’s perspective on comparison. There is also a lot of quality data available from the case company that can be compared to the answers received. According to the results of the study there are some differences between current status of quality perspective between case company and suppliers and cooperation can be made working smoothly and effectively between company and small Finnish suppliers. In the future, it could be explored how possible changes occurring in this work affect the atmosphere and effectiveness of cooperation.

TIIVISTELMÄ : Tämän tutkimuksen tarkoitus on tutkia laatuyhteistyötä tutkimuksen kohteena olevan yhtiön ja joidenkin sen pienten Suomalasten alihankkijoiden välillä. Tutkimuksen tekijä on töissä tutkittavassa yhtiössä. Yhtiö on tunnistanut tarpeen tämän kaltaiselle tutkimukselle. Monilla osa-alueilla on havaittu näkemyseroja koskien yhteistyön ja kommunikaation vaikutusta laatuun. Tutkimuksessa keskitytään enemmän alihankkijoiden näkemykseen laatuyhteistyöstä. Teoreettisessa osassa tarkastellaan taustaa tutkimalla kirjallisuutta yhteistyön dynamiikasta ja tehostamisesta, laadun kehittämisestä tämän tapauksen yhteydessä ja mahdollisesti viestinnästä hierarkkisessa ympäristössä. Empiirisen osuuden haastattelut on toteutettu kasvokkain. Haastattelu tehtiin neljässä pohjalaisyrityksessä. Kaksi työntekijää joka yhtiöstä on haastateltu. Haastattelut on nauhoitettu ja tämän jälkeen analysoitu. Myös kaksi ihmistä tutkittavan yrityksen eri osastoilta on haastateltu, jotta on saatu yrityksen näkökulma mukaan vertailuun. Tutkittavassa yrityksessä on myös paljon dataa saatavilla vertailtavaksi haastatteluista saatuihin tuloksiin. Tutkimuksesta saatujen tulosten valossa on havaittavissa joitakin näkemys eroja laadun tilasta yhtiöiden välisessä laatuyhteistyössä. Keinoja yhteistyön sujuvoittamiseksi ja tehostamiseksi yhtiöiden välillä on löydetty. Tulevaisuudessa voitaisiin tutkia miten tämän tutkimuksen yhteydessä löydetyt muutokset vaikuttavat yhteistyön ilmapiiriin ja tehokkuuteen.
Keywords: quality; cooperation (general); quality management; suppliers; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management